READING CAN BE FUN AND AN ACTIVE ACTIVITY: A CASE OF UNIOESTE EFL STUDENTS - Sardo, Cláudia Estima; Escher, Juliana (Revista Expectativa, 2000)
This article discusses the active role of reading form an analysis of a group of university students. A profile resulted from this investigation pointing out students’ likes and dislikes, their habits and suggestions for interesting classes. The results suggest that pre-reading and post-reading activities involving some type of physical expressing should be introduced in the classes.